CP Rail Tunnels In The Rogers Pass, British Columbia, Canada - Ronald S. Tanaka (Society for Mining, Metallurgy & Exploration, 1987)
In the planning stages for a dozen years, the 9.11 mile long Mount Macdonald Tunnel is the focal point of the $600 million dollar Rogers Pass Project. The paper will discuss the construction of the tunnel that is being carried out from both ends. The eastern portion contractor has used a tunnel boring machine to excavate the upper part of the tunnel and at the west end contractor selected the conventional drill and blast method. A ventilation shaft located near the mid point is the main part of a ventilation system unique in the Western Hemisphere.